Psilido de la papa - International Potato Center (2025)
This short video highlights the importance of orange-fleshed sweetpotato (OFSP) as a nutritious and climate-resilient crop that supports food security, improved nutrition, and livelihoods. Rich in vitamin A, OFSP contributes to reducing micronutrient deficiencies while offering income opportunities for smallholder farmers. The video reinforces CIP’s commitment to strengthening sweetpotato agri-food systems through biofortification, seed systems, and nutrition-sensitive agriculture.